2015
DOI: 10.1038/nn.4155
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal activity is not required for the initial formation and maturation of visual selectivity

Abstract: Neuronal activity is important for the functional refinement of neuronal circuits in the early visual system. At the level of the cerebral cortex, however, it is still unknown whether the formation of fundamental functions such as orientation selectivity depends on neuronal activity, as it has been difficult to suppress activity throughout development. Using genetic silencing of cortical activity starting before the formation of orientation selectivity, we found that the orientation selectivity of neurons in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
82
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(95 citation statements)
references
References 59 publications
13
82
0
Order By: Relevance
“…Importantly, visual experience is required for this maturation (Li et al, 2006). Seemingly in contrast, in the mouse, Hagihara et al (2015) found that the proportion of responsive and orientation-selective cells is mature at eye opening. This is in line with findings from Ko et al (2013) but unlike Rochefort et al (2011) where a gradual increase in responsiveness and selectivity was reported.…”
Section: Spontaneous Activity Helps Wire the Developing Sensory Systemmentioning
confidence: 95%
See 4 more Smart Citations
“…Importantly, visual experience is required for this maturation (Li et al, 2006). Seemingly in contrast, in the mouse, Hagihara et al (2015) found that the proportion of responsive and orientation-selective cells is mature at eye opening. This is in line with findings from Ko et al (2013) but unlike Rochefort et al (2011) where a gradual increase in responsiveness and selectivity was reported.…”
Section: Spontaneous Activity Helps Wire the Developing Sensory Systemmentioning
confidence: 95%
“…This early selectivity is independent of any visual experience as it is not prevented by dark-rearing (Rochefort et al, 2011), suggesting that spontaneous activity may mediate orientation and direction selectivity. Surprisingly, a recent study found that blocking spontaneous activity during development in mice did not reduce orientation selectivity (Hagihara et al, 2015). Spontaneous activity was blocked in L2/3 of the visual cortex, by expressing the inward rectifying potassium channel Kir 2.1 through in utero electroporation.…”
Section: Spontaneous Activity Helps Wire the Developing Sensory Systemmentioning
confidence: 98%
See 3 more Smart Citations